Analisis Nilai Kenusantaraan dan Self Improvement dalam Pakêliran Wayang Gêdhog Gaya Surakarta - Farizky, Muhammad Thoriq Akbar; Afiva, Shinta Miswatul; Pangesti, Septiana Dian (Arnawa, 2024)
Wayang gêdhog is one of the mediums of Panji Stories in the form of wayang kulit with rare performances that are thick with Nusantara archipelago nuances. This study aims to determine the values in the Surakarta style of wayang gêdhog performance after its revitalization in 2014 as a representation of its preservation as a solace for society and the nation. This research is qualitative descriptive research with a social psychology approach. Theory in social psychology is used to analyze values, both from an Nusantara archipelago perspective and self-improvement in the Surakarta style of wayang gêdhog performance. This research shows the results of the contents of Nusantara archipelago values and self-improvement that are relevant for the younger generation in their daily lives as individuals and the life of their nation during post-Covid-19 recovery. The conclusion that can be known is that wayang gêdhog has Nusantara archipelagic values which teach peace and harmony in the Nusantara archipelago, inter-tribal cooperation, unity in diversity, equal rights or equality, active free views, fertility as a balance of nature, and purification towards sacredness. Meanwhile, the value of self-improvement invites one to develop through lateral thinking, self-potential development, remaining productive while recovering, self-motivation through history, the importance of focusing on process rather than results, as well as non-linear habits and professionalism. === Wayang gêdhog adalah salah satu medium Cerita Panji berbentuk wayang kulit dengan pementasan langka yang kental dengan nuansa kenusantaraan. Penelitian ini bertujuan untuk mengetahui nilai-nilai dalam pagelaran wayang gêdhog gaya Surakarta pasca revitalisasinya di tahun 2014 sebagai representasi pelestariannya sebagai pelipur lara bagi masyarakat dan bangsa. Penelitian ini berjenis penelitian deskriptif kualitatif dengan pendekatan psikologi sosial. Teori dalam psikologi sosial dipakai untuk menganalisis nilai-nilai, baik dari sisi kenusantaraan maupun self improvement dalam pagelaran wayang gêdhog gaya Surakarta. Penelitian ini memperlihatkan hasil kandungan-kandungan nilai kenusantaraan dan self improvement yang relevan bagi generasi muda dalam kehidupan keseharian sebagai individu dan kehidupan berbangsanya di kala pemulihan pasca Covid-19. Kesimpulan yang dapat diketahui yakni wayang gêdhog memiliki nilai-nilai kenusantaraan yang mengajarkan perdamaian dan kerukunan bangsa Nusantara, kerja sama antarsuku bangsa, bhinneka tunggal ika, persamaan hak atau kesetaraan, pandangan bebas aktif, kesuburan sebagai keseimbangan alam, serta penyucian menuju sakralitas. Sedangkan nilai self improvement mengajak untuk mengembangkan diri melalui berpikir lateral, pengembangan potensi diri, tetap produktif sembari recovery, motivasi diri melalui sejarah, pentingnya fokus pada proses dibanding hasil, serta non-linear habit dan profesionalisme.